Ultraviolet light aging properties of PVC/CaCO3 composites. Issue 4 (16th May 2012) - Liu, Hai; Dong, Lijie; Xie, Haian; Wan, Lipeng; Liu, Zhukai; Xiong, Chuanxi
Abstract The ultraviolet radiation aging behaviors of PVC/CaCO3 and PVC/CaCO3/macromolecular modifier composites were studied through whiteness measurement, Fourier transform infrared spectroscopy, ultraviolet–visible spectroscopy, scanning electron microscopy, and mechanical properties test. It was found that nano‐CaCO3 particles used as ultraviolet light screening agents could significantly enhance the antiaging properties of PVC materials. Due to the macromolecular modifier coated on nano‐CaCO3 particles, the compatibility of nano‐CaCO3 and PVC matrix was improved, resulting in uniform dispersion of nano‐CaCO3 in PVC matrix. Therefore, the PVC/CaCO3/MP composite exhibited better antiaging properties than PVC/CaCO3 composite. After 12 h of ultraviolet irradiation, the tensile strength retention, elongation at break retention, and impact strength retention of PVC/CaCO3/MP composite were 79.5%, 74.5%, and 75.3%, which were much higher than that of neat PVC and PVC/CaCO3 composite. © 2012 Wiley Periodicals, Inc. J. Appl. Polym. Sci., 2013